2015
DOI: 10.1177/0954407014564690
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the moan noise by frequency-response-function-based substructuring and optimization techniques

Abstract: ‘Moan’ noise in a vehicle causes discomfort and anxiety to passengers. In the previous study, the causes of moan noise were identified, and a coherence analysis of the components was conducted. It was found that moan noise was generated by the attribution of resonance when the exciting force produced by the stick–slip motion in a brake system was transmitted to a coupled torsional beam axle module. The analysis involved calculation of the response of the coupled torsional beam axle module on a full suspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The results indicated that the effect of friction coefficients played a significant role on the generation of brake noise, and the instability of the brake system increased with the higher value of friction coefficient. Kim,et al,9 replicated the moan noise during the vehicle's operating test and identified that the resonance of the beam axle module, due to the exciting force of the brake system, is the main cause of moan noise. They conducted both coherence and transfer path analysis to identify how the vibrations from the beam axle module were related to moan noise.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the effect of friction coefficients played a significant role on the generation of brake noise, and the instability of the brake system increased with the higher value of friction coefficient. Kim,et al,9 replicated the moan noise during the vehicle's operating test and identified that the resonance of the beam axle module, due to the exciting force of the brake system, is the main cause of moan noise. They conducted both coherence and transfer path analysis to identify how the vibrations from the beam axle module were related to moan noise.…”
Section: Introductionmentioning
confidence: 99%